2016
DOI: 10.3389/fpsyg.2016.01495
|View full text |Cite
|
Sign up to set email alerts
|

To Be or Not To Be Humorous? Cross Cultural Perspectives on Humor

Abstract: Humor seems to manifest differently in Western and Eastern cultures, although little is known about how culture shapes humor perceptions. The authors suggest that Westerners regard humor as a common and positive disposition; the Chinese regard humor as a special disposition particular to humorists, with controversial aspects. In Study 1, Hong Kong participants primed with Western culture evaluate humor more positively than they do when primed with Chinese culture. In Study 2a, Canadians evaluate humor as being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 43 publications
1
63
1
1
Order By: Relevance
“…That is, Turkish students' preference over humor-oriented English teachers was significantly higher than that of Asian students. One possible explanation for this difference might be the stratified structure of the teacher-student rapport in Asian, particularly Chinese, culture (Chen & Martin, 2007;Yue et al, 2016;Zhang, 2005). Contrary to this, Turkish students may find humorous English teachers quite approachable when they attempt to use non-serious language in serious and often teacher-fronted language teaching environments.…”
Section: Discussionmentioning
confidence: 99%
“…That is, Turkish students' preference over humor-oriented English teachers was significantly higher than that of Asian students. One possible explanation for this difference might be the stratified structure of the teacher-student rapport in Asian, particularly Chinese, culture (Chen & Martin, 2007;Yue et al, 2016;Zhang, 2005). Contrary to this, Turkish students may find humorous English teachers quite approachable when they attempt to use non-serious language in serious and often teacher-fronted language teaching environments.…”
Section: Discussionmentioning
confidence: 99%
“…Blair [44] reported that humor is considered in the eastern societies as a profession and believed to be done by professionals and that those outside this profession prefer staying away from humor. Yue [45] have found that Chinese students defined humor as deviation from seriousness and with negative adjectives but humor was considered an indispensable part of daily life and defined with positive adjectives in Western societies, particularly in America.…”
Section: Discussionmentioning
confidence: 99%
“…In many studies involving intercultural comparison as related to humor, the Chinese sample and the American and Canadian samples are compared. In the overall evaluation, it was found that American university students mention humor with positive adjectives and see it as an indispensable part of daily life while Chinese university students use negative adjectives and see humor far from seriousness [45].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, we hypothesize that students may find jokes about their own in-group offensive but perceive jokes about individuals who are not part of their in-group as funny. Additionally, one's native language can affect how one perceives and interprets humor (29)(30)(31)(32). If someone is exposed to humor in another language it may diminish their ability to interpret the humor as intended, particularly ironic humor or humor that uses word play such as puns (31,33,34).…”
Section: An Example Of [One Of] His Pun[s] Included a Picture Of A Goatmentioning
confidence: 99%